Factors against senior secondary school students' performance in english writing skills: the teachers and learners' perspectives (2023)
Writing skills are essential for academic success and effective communication in today's interconnected world. This study investigates the factors influencing senior secondary school students' writing performance in English in Ibadan North Local Government Area, Nigeria, from the perspectives of both teachers and students. Despite the importance of writing, students face challenges that raise concerns among examination bodies like WAEC and NECO regarding their writing competencies. Identified factors include socioeconomic influences, psychological barriers, ineffective instructional methods, and the impact of technology and social media. The research utilized a sequential exploratory mixed-methods design, involving 300 students and 10 teachers from selected public schools. Key findings indicate that poor family backgrounds, lack of parental support, and inadequate teacher training substantially hinder writing abilities. Psychological factors, such as fear of criticism and low self-efficacy, along with social media influence, further complicate writing development. The study recommended targeted interventions, such as improved teacher training, increased parental involvement, and the integration of technology in writing instruction, to create an environment conducive to developing strong writing skills and enhancing academic performance.